Phorbol ester inhibits angiotensin-induced activation of phospholipase C in adrenal glomerulosa cells. Its implication in the sustained action of angiotensin. - Kojima, I (1986)
The present study was undertaken to determine whether an agonist-induced activation of C-kinase leads to an inhibition of phospholipase C in adrenal glomerulosa cells. When cells are treated with 100 nM-TPA (12-O-tetradecanoylphorbol 13-acetate), subsequent angiotensin ('angiotensin II')-induced aldosterone secretion is greatly inhibited. Treatment with TPA completely inhibits the angiotensin-induced increase in both inositol trisphosphate and the cytosolic Ca2+ concentration. The dose-response curve for TPA-induced inhibition reveals that quite a high concentration of TPA is necessary to block angiotensin action compared with that needed to stimulate aldosterone secretion. 1-Oleoyl-2-acetylglycerol has a weak inhibitory effect, whereas neither 4 alpha-phorbol 12,13-didecanoate or 4 beta-phorbol inhibits angiotensin action. When the time course of changes in inositol trisphosphate and diacylglycerol is measured, angiotensin action is sustained for up to 30 min. In addition, 100 nM-TPA added after 20 min of angiotensin addition attenuates production of both inositol trisphosphate and diacylglycerol. These results suggest that high dose of TPA inhibits angiotensin-induced activation of phospholipase C by acting, at least partly, on C-kinase, but that an inhibitory effect of TPA may be a pharmacological effect with little physiological significance in this system.